TỔNG HỢP POLYME SIÊU HẤP THỤ NƯỚC TRÊN CƠ SỞ MỘT SỐ COPOLYME GHÉP TINH BỘT - Tùng, Nguyễn Thanh; Khôi, Nguyễn Văn; Đức, Nguyễn Trung; Hoan, Đỗ Công (Vietnam Journal of Chemistry, 2012)
The superabsorbent polymers (SAPs) were synthesized by graft polymerization of acrylic acid (AA) and acrylamide (AM) onto tapioca starch (AMS-1 and AMS-2, respectively) using potassium persulfate (KPS) as initiator and N,N’- methylenebisacrylamide (MBA) as crosslinker. The effects of reaction conditions, such as reaction temperature, crosslinker and initiator contents, starch content and degree of neutralization on the water absorbency were also investigated. Surface morphology of 2 samples of SAP was characterized by SEM.